Working Time and Work Intensity in Portuguese Courts - Dias, João Paulo (2024)
This article examines working conditions among court clerks, public prosecutors, and judges in Portugal, based on the results of an online questionnaire and interviews, developed at the research project QUALIS. It focuses on two dimensions of working conditions: working time and work intensity. The results show that Portuguese judicial professionals work at a high pace and outside regular hours to achieve a heavy workload to tight deadlines. These working conditions are seen, or experienced, as inevitable, to be expected, and normalized. This article invite to take into consideration these results in order to improve the performance of courts and the quality of justice provided to citizens.